2007
DOI: 10.1017/s1368980007360928
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency and brain development in the first half of pregnancy

Abstract: An inadequate supply of iodine during gestation results in damage to the foetal brain that is irreversible by mid-gestation unless timely interventions can correct the accompanying maternal hypothyroxinemia. Even mild to moderate maternal hypothyroxinemia may result in suboptimal neurodevelopment. This review mainly focuses on iodine and thyroid hormone economy up to mid-gestation, a period during which the mother is the only source for the developing brain of the foetus. The cerebral cortex of the foetus depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
218
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(234 citation statements)
references
References 111 publications
(230 reference statements)
4
218
0
12
Order By: Relevance
“…Other potential indices of ID, such as neonatal TSH, are not completely reliable due to many factors, including the timing of sample collection (1)(2)(3)(4)32,35,36). Although the present study showed that the newborns met the WHO criteria for desirable serum TSH concentrations (considered iodine sufficient if less than 3% of the newborns have TSH >5 mU=L), it is now well recognized that the regulation of TSH secretion in the newborn does not follow the same feedback mechanisms observed when the thyroid-pituitary axis is fully developed (6). Therefore, the cutoffs for defining severity of ID on the basis of newborn TSH concentrations originally proposed by the WHO have been questioned and are not considered in most of the recent recommendations (3).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Other potential indices of ID, such as neonatal TSH, are not completely reliable due to many factors, including the timing of sample collection (1)(2)(3)(4)32,35,36). Although the present study showed that the newborns met the WHO criteria for desirable serum TSH concentrations (considered iodine sufficient if less than 3% of the newborns have TSH >5 mU=L), it is now well recognized that the regulation of TSH secretion in the newborn does not follow the same feedback mechanisms observed when the thyroid-pituitary axis is fully developed (6). Therefore, the cutoffs for defining severity of ID on the basis of newborn TSH concentrations originally proposed by the WHO have been questioned and are not considered in most of the recent recommendations (3).…”
Section: Discussionmentioning
confidence: 59%
“…Particularly important is the role of thyroid hormones in normal brain development and cognition. It has been shown that insufficient iodine intake during pregnancy and lactation and in newborns may lead to irreversible brain damage (1)(2)(3)(4)(5)(6)(7)(8)(9). The severity of this impairment varies from cretinism, in regions of severe iodine deficiency (ID), to the inability of children to achieve their potential intelligence quotient, when iodine intake is mildly to moderately insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a critical period of organ growth and maturation, and thus, not surprisingly, T3 deficiency during this period causes severe developmental defects (5,11,12). Interestingly, appropriate levels of maternal T3 are also important to ensure proper mammalian development (13)(14)(15). These observations suggest that proper levels of T3 in both the mother and fetus are critical for mammalian development, which makes it difficult to separate the direct effects of T3 on the development of the fetus versus indirect effects through maternal influence.…”
Section: Thyroid Hormone (T3)mentioning
confidence: 99%
“…The effect of reduced thyroid function on fetal development appears to be the most severe during the first trimester of pregnancy (Kooistra et al, 2006;Morreal de Escobar et al, 2007). Even relatively modest reductions in thyroid hormone levels in early pregnancy may be associated with adverse effects on fetal nervous system (Pop et al, 1999(Pop et al, , 2003Kooistra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%